THE METHODS OF DISTINCTION OF ACCESSORY MINERALS OF GOLD IN ACCORDANCE WITH GRADE OF THEIR IMPORTANCE IN CONGLOMERATES - Shestakov, O.Yu. (Institute of Geological Sciences, NAS of Ukraine, 2019)
Accessory minerals of gold in conglomerates, as well as gold itself, are breaked up into two groups: allothigenic (inherited from mother rocks) and authigenic (formed in sedimentary rock after its formation) relatively to genesis of them. Allothigenic and authigenic accessory minerals have different and unequal significance as the search signs of gold metallization. Therefore, there is a need for a methodology for distinguishing of the origin of the accessory minerals of gold in these rocks. The difference of the genesis of the the accessory minerals of gold is reflected in the difference of the character of relationship of gold with them. The different character of relations of gold with allothigenic (zircon, ilmenite, apatite) and authigenic (pyrite) accessory mineralization in these rocks (the gold-bearing conglomerates of the Bilokorovichy structure of the Volyn block of the Ukrainian shield are mentioned as an instance) is pointed out. The difference of the relationship character of gold with the accessory minerals of it come out in different: a) configurations of accumulation areas of points for plotting the relationship of the concentration of gold and its associated minerals; b) the angles of inclination of these graphs. The common origin of the accessory minerals of gold in the conglomerates is showed by the proximity of these indicators. The method of distinguishing of different genesis accessory minerals of gold applying correlation-regressional analysis is proposed. It consists in the fact that using the angular coefficients in the regression equations describing the relationship of gold with the accessory minerals, the slope angles of the regression graphs corresponding to this equation are determined. Then, comparing the proximity of the slope angles, the conclusion about allotigenicity (syngeneticity) or autogenicity (epigeneticity) of the accessory minerals of gold metallization is made.